Optimization of biosynthesis parameters for antibiotic production by S. cyanogenus S137 in laboratory conditions - Syromiatnykov Yurii; Radjabov Jamol; Voinash Sergey; Vashchilin Viktor; Orekhovskaya Alexandra; Vanzha Vladimir; Akhtyamova Leisan (BIO Web of Conferences)
In this study, the conditions for the submerged biosynthesis of the antibiotic landomycin A by the strain Streptomyces cyanogenus S137 were investigated. Various nutrient media based on soybean and corn extracts were tested to enhance product yield. Optimal fermentation parameters, including temperature, stirring speed, and fermentation duration, were established. The study demonstrated that modifications in nutrient components and cultivation conditions allow for an antibiotic yield of up to 80 μg/ml, with a significant reduction in media cost. The most effective conditions were a temperature of 25 ± 1°C and a stirring intensity of 230 rpm. The results showed that using corn flour and soybean extract as alternative components to expensive soy tryptone significantly improves biosynthesis efficiency while lowering production costs. Additionally, the strain exhibited a high demand for aeration, achieved through increased agitation speed. The findings provide valuable insights for optimizing the industrial production of landomycin A and demonstrate the potential of cost-effective nutrient media in large-scale antibiotic production. This research contributes to the advancement of microbial biotechnology and offers practical approaches to enhancing the economic viability of antibiotic manufacturing in industrial settings.